2023
DOI: 10.3389/fonc.2022.1007146
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of tumor mutation burden in patients with advanced gastric cancer receiving first-line chemotherapy

Abstract: BackgroundTumor mutation burden (TMB) is a promising biomarker positively associated with the benefit of immunotherapy and that might predict the outcome of chemotherapy. We described the prognostic value of TMB in advanced gastric cancer and explored the underlying mechanism.MethodsWe enrolled 155 TMB-evaluated advanced gastric cancer patients and analyzed the relationship between clinicopathological characteristics and both overall survival (OS) and progression-free survival (PFS) among 40 patients treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(58 reference statements)
0
0
0
Order By: Relevance
“…McGrail et al reported that onesize-fits-all high-TMB cut point could not applied for predicting ICIs efficacy for all types of tumors (McGrail et al, 2021). Several cutoff values have been used to define high TBM in GC by different studies (Wang et al, 2019;Duan et al, 2022). In 2020, pembrolizumab was approved for the treatment of metastatic GC with high-TMB (≥10 mut/Mb) by the US Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%
“…McGrail et al reported that onesize-fits-all high-TMB cut point could not applied for predicting ICIs efficacy for all types of tumors (McGrail et al, 2021). Several cutoff values have been used to define high TBM in GC by different studies (Wang et al, 2019;Duan et al, 2022). In 2020, pembrolizumab was approved for the treatment of metastatic GC with high-TMB (≥10 mut/Mb) by the US Food and Drug Administration.…”
Section: Discussionmentioning
confidence: 99%